1994
DOI: 10.1104/pp.106.2.559
|View full text |Cite
|
Sign up to set email alerts
|

A Group of Chromosomal Proteins Is Specifically Released by Spermine and Loses DNA-Binding Activity upon Phosphorylation

Abstract: Biologically relevant concentrations as low as 500 PM spermine led to the specific release of chromatin-associated proteins from nuclei of rice (Oryza sativa) seedlings. Using a southwestern technique, it was shown that several of these proteins bind DNA. This affinity was lost upon in organello phosphorylation by an endogenous kinase. The effect of spermine was very specific. Spermidine was far less effective and putrescine was essentially ineffective in releasing these proteins. The most abundant spermine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…It is well known that the physiological-biochemical activity of di-and polyamines is mainly due to their polycation structure. In all probability, the more number of amine groups in poliamine, the more metabolically active this compound is, because in this way it possesses greater biochemical possibilities to interact with nucleic acids, proteins, hormones and another metabolites characterised by regulating function (Van den Broeck et al 1994;Davis 1997;Tiburcio et al 1997;Laitinen et al 1998;Desideiro et al 1999;Kotzabasis et al 1999). From the studies carried out on the C. vulgaris it was seen that the highest biological activity of spermidine results from the fact that it contains three amine groups of a cation character whereas the lowest activity is noted in agmatine with only one -NH 2 group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the physiological-biochemical activity of di-and polyamines is mainly due to their polycation structure. In all probability, the more number of amine groups in poliamine, the more metabolically active this compound is, because in this way it possesses greater biochemical possibilities to interact with nucleic acids, proteins, hormones and another metabolites characterised by regulating function (Van den Broeck et al 1994;Davis 1997;Tiburcio et al 1997;Laitinen et al 1998;Desideiro et al 1999;Kotzabasis et al 1999). From the studies carried out on the C. vulgaris it was seen that the highest biological activity of spermidine results from the fact that it contains three amine groups of a cation character whereas the lowest activity is noted in agmatine with only one -NH 2 group.…”
Section: Resultsmentioning
confidence: 99%
“…A few reports (Smith 1985;Dureja-Munjal et al 1992; Van den Broeck et al 1994;Ye et al 1994;Ponappa and Miller 1996;Bagni 1997) showed that di-and polyamines activate the synthesis of secondary cellular signal transmitters, e.g. triphosphoinositol and diacylglycerol mainly by stimulating the synthesis of their direct precursors, the phosphoinositides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the single HMGB-box, DNA binding is enhanced when the two domains are covalently connected (A+B) in vitro (Reddy et al, 2005; Stros, 1998, 2001; Yoshioka et al, 1999). Binding of HMGB1 to DNA is also regulated by post-translational modifications (e.g., phosphorylation, acetylation, and oxidization) (Assenberg et al, 2008), pH, ions (e.g., calcium and Mg 2+ ) (Makiguchi et al, 1984; Stros et al, 1990) and the presence of another cationic factor, spermine (Van den Broeck et al, 1994). pH affects interactions between DNA and high-mobility group protein HMG1 (Kohlstaedt and Cole, 1994a).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…lanes 1 and 4), much smaller proportions of HMGc and HMGd (Ͻ25%) were extracted (lanes 8 and 12). Accordingly, a protein similar to maize HMGa had been reported to be specifically extracted from rice chromatin by spermine ( Van den Boeck et al, 1994). The molecular mechanism(s) responsible for the specific extraction of HMGa (compared with the structurally similar HMGc and HMGd) by spermine remains to be established.…”
Section: Differential Release Of the Maize Hmg1-like Proteins From Chmentioning
confidence: 99%